2005
DOI: 10.1172/jci24061
|View full text |Cite
|
Sign up to set email alerts
|

Loss of receptor-mediated lipid uptake via scavenger receptor A or CD36 pathways does not ameliorate atherosclerosis in hyperlipidemic mice

Abstract: Macrophage internalization of modified lipoproteins is thought to play a critical role in the initiation of atherogenesis. Two scavenger receptors, scavenger receptor A (SR-A) and CD36, have been centrally implicated in this lipid uptake process. Previous studies showed that these receptors mediated the majority of cholesterol ester accumulation in macrophages exposed to oxidized LDL and that mice with deletions of either receptor exhibited marked reductions in atherosclerosis. This work has contributed to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
275
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(295 citation statements)
references
References 47 publications
18
275
1
1
Order By: Relevance
“…Because of recognition of the extensive remodeling at the aortic sinus, we have felt that it is more appropriate to measure aortic tree lesion area to assess atherosclerosis extent in Western diet fed mice in our studies. Re-examination of the data of Moore et al (2005) then shows similar results to what we reported in the aortic tree; the difference in males may manifest more strongly at 12 weeks rather than 8 weeks.…”
Section: Cd36 and Insulin Resistancesupporting
confidence: 85%
See 2 more Smart Citations
“…Because of recognition of the extensive remodeling at the aortic sinus, we have felt that it is more appropriate to measure aortic tree lesion area to assess atherosclerosis extent in Western diet fed mice in our studies. Re-examination of the data of Moore et al (2005) then shows similar results to what we reported in the aortic tree; the difference in males may manifest more strongly at 12 weeks rather than 8 weeks.…”
Section: Cd36 and Insulin Resistancesupporting
confidence: 85%
“…The view that scavenger receptors (specifically CD36 and SRA) contribute to foam cell formation, particularly in a pro-inflammatory setting, which promotes lipoprotein modifications that enhance their specific recognition by such receptors, was questioned recently in a report by Moore et al (2005). In that study, CD36/apoE double KO mice were fed a Western diet for 8 weeks and lesions evaluated at both the aortic sinus and throughout the aortic tree.…”
Section: Cd36 and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Among these SRs, the type A scavenger receptor (SRA) and CD36, a member of the type B family, have been extensively studied (Kunjathoor et al, 2002). It is well known that ApoE-deficient mice, which are widely used as a model of atherosclerosis, develop atherosclerotic lesions throughout the arterial tree (Moore et al, 2005;Manning-Tobin et al, 2009). Interestingly, mice with CD36 and ApoE double deficiency show reduced atherosclerotic lesions and greatly reduced uptake of oxLDL by macrophages compared with their littermate controls © Higher Education Press and Springer-Verlag Berlin Heidelberg 2012 (Podrez et al, 2000).…”
Section: Lipoprotein Uptakementioning
confidence: 99%
“…Furthermore, AGE induce endothelial hyperpermeability and have been shown to be chemotactic for monocytes in vitro and in vivo [17]. Although the role of scavenger receptors in atherogenesis is controversial [19], induction of scavenger receptor class A and CD36 in macrophages due to AGE may represent another pro-atherogenic mechanism [17]. In summary, AGE formation due to hyperglycemia may promote development of atherosclerotic lesions by various well-known pro-atherogenic receptors [20].…”
Section: Advanced Glycation End Products (Age)mentioning
confidence: 99%